Commonsense Darwinism: evolution, morality, and the human condition - Lemos, John (Open Court, 2008)
Introduction -- Defending a socio-biological account of morality -- Non-objectivist evolutionary ethics -- Recent objectivist approaches to evolutionary ethics -- Sketch of an Aristotelian evolutionary ethics -- Evolutionary biology and the moral status of animals -- Faith, reason, and evolutionary epistemology -- Psychological egoism and evolutionary biology -- Evolution and free will : darwinian non-naturalism defended -- Recent developments in philosophy of evolution